2016
DOI: 10.1116/1.4954789
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion kinetics of human primary monocytes, dendritic cells, and macrophages: Dynamic cell adhesion measurements with a label-free optical biosensor and their comparison with end-point assays

Abstract: Monocytes, dendritic cells (DCs), and macrophages (MFs) are closely related immune cells that differ in their main functions. These specific functions are, to a considerable degree, determined by the differences in the adhesion behavior of the cells. To study the inherently and essentially dynamic aspects of the adhesion of monocytes, DCs, and MFs, dynamic cell adhesion assays were performed with a high-throughput label-free optical biosensor [Epic BenchTop (BT)] on surfaces coated with either fibrinogen (Fgn)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…Studying the spreading of macrophages we found that anti-CR4 also inhibited this function of these human cells. [17,124,125]. Immune cells of the monocytic lineage use specific adhesive structures for cell migration, called podosomes.…”
Section: Mfmentioning
confidence: 99%
“…Studying the spreading of macrophages we found that anti-CR4 also inhibited this function of these human cells. [17,124,125]. Immune cells of the monocytic lineage use specific adhesive structures for cell migration, called podosomes.…”
Section: Mfmentioning
confidence: 99%
“…The possibility to chemically modify the sensing surface allows for the examination of specific molecular interactions, such as Arg-Gly-Asp tripeptide (RGD motif) mediated activation and clustering of integrin proteins. The high-quality data provided by this technique have found its use in various fields such as receptor biology [49][50][51] , immune cell biology 52 , environmental toxicology 53 , or the testing of natural active compounds 22,[54][55][56] . Depending on their configuration, RWG sensors are generally compatible with standard 96-or 384-well plates, providing a platform for high-throughput measurements, where numerous cell populations can be measured at the same time under different conditions.…”
mentioning
confidence: 99%
“…The copolymer and its cell adhesive, functionalized counterpart, PLL- g -PEG-RGD can be mixed to vary the cell adhesion ligand density at the nanoscale, and to induce cell adhesion and spreading on the coated surfaces. Here, we use the mixture of PLL- g -PEG and PLL- g -PEG-RGD to control the spreading abilities of the monitored cells 26 27 . Note, PLL- g -PEG is often considered as a gold standard of antifouling surfaces, but the interaction of these coatings with polyphenols has never been investigated.…”
mentioning
confidence: 99%